Controlled growth of SnO2 nanostructures with small diameters and their photocatalytic properties. (1st August 2013) - Cheng, Guoe; Hao, Tingting; Ke, Hanzhong; Gong, Fujun; Chen, Jinyan; Shang, Jin
Abstract : SnO2 nanocrystals with small diameters including nanorods, nanowires connected by nanorods and nanoparticles have been obtained in mixed solvents of oleic acid (OA) and ethanol. By simply adjusting the volume ratio of these solvents, the morphologies and structures of the SnO2 crystals can be easily varied. All the products show pure tetragonal SnO2 with a rutile structure and the obtained nanorods can be connected with each other in various ways to form nanowires. The nanocrystals with a volume ratio of OA and ethanol of 1:1 present the best photocatalytic properties which shows 100% degradation of Rhodamine B within 60 min.